2013
DOI: 10.1130/ges00925.1
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Although Basin and Range-style extension affected large areas of western Mexico after the Late Eocene, most consider that extension in the Gulf of California region began as subduction waned and ended ca. 14-12.5 Ma. A general consensus also exists in considering Early and Middle Miocene volcanism of the Sierra Madre Occidental and Comondú Group as subduction related, whereas volcanism after ca. 12.5 Ma is extension related. Here we present a new regional geologic study of the eastern Gulf of California margin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(41 citation statements)
references
References 126 publications
(235 reference statements)
1
31
0
9
Order By: Relevance
“…This is problematic for dating the younger (early Miocene) rocks, which often contain 'antecrysts', zircons that formed during earlier phases of related magmatism within the igneous province but are not directly crystallized from the host magma (e.g. Ferrari et al 2013;Murray et al 2013). Where mixed-age populations are suggested (e.g.…”
Section: Depositional Age Constraints Methodology and Age Interpretationsmentioning
confidence: 98%
See 1 more Smart Citation
“…This is problematic for dating the younger (early Miocene) rocks, which often contain 'antecrysts', zircons that formed during earlier phases of related magmatism within the igneous province but are not directly crystallized from the host magma (e.g. Ferrari et al 2013;Murray et al 2013). Where mixed-age populations are suggested (e.g.…”
Section: Depositional Age Constraints Methodology and Age Interpretationsmentioning
confidence: 98%
“…In our analyses, we interpret the oldest zircon age population calculated using this method that is less than ca. 38 Ma in a sample represents the crystallization age of antecrysts incorporated into the host magma and that the youngest zircon age population indicates the age of phenocryst crystallization (after Ferrari et al 2013), which we interpret as the maximum possible eruption age of the rock. Age results are presented in the following and summarized in Figure 10 and Table 2, with the locations of the samples shown in Figure 3 and Plate 1; detailed analytical data are given in Supplemental …”
Section: Depositional Age Constraints Methodology and Age Interpretationsmentioning
confidence: 99%
“…The Gulf of California is a complex zone of oblique extension, where extension in the southern segments may have initiated in the Mid to Late Miocene (Ferrari et al, 2013), and extension along the whole Gulf was fully underway from 12.5 Ma (e.g., Atwater & Stock, 1998), where current relative motion of the Baja Microplate and the North American plate is between 45 and 47 mm yr 21 (Plattner et al, 2007). In the model-observation comparison, Figure 9, we assume extension started at 18 Ma.…”
Section: Gulf Of Californiamentioning
confidence: 99%
“…In the model-observation comparison, Figure 9, we assume extension started at 18 Ma. In the Sinaloa region toward the south of the Gulf of California, there is a set of dated lavas with REE compositions (Ferrari et al, 2013), which allow for a model comparison. Off-shore of Sinaloa, within the Alarc on and Capo to Puerto Vallarta transects, the oceanic crust is 5 km thick (Lizarralde et al, 2007) and the transition from continental to oceanic crust is wide, particularly at the Alarc on transect (Lizarralde et al, 2007;Sutherland et al, 2012), although this larger width in transition may be partially due to the formation of a failed oceanic basin (Abera et al, 2016).…”
Section: Gulf Of Californiamentioning
confidence: 99%
“…The panels defi ned by Henry et al (2010) include the Great Basin (shown on Fig. 3A), as well as Southern Rocky Mountain, Mogollon-Datil, Trans-Pecos volcanic fi elds of the U.S. (not shown) and the Sierra Madre Occidental of Mexico (also not shown; see Murray et al, 2013;Ferrari et al, 2013). Eocene to Miocene slab fallback and arc extension associated with it in Mexico ultimately led to Miocene rifting in the Gulf of California (Ferrari et al, 2007.…”
Section: Extensional Arc (50-13 Ma)mentioning
confidence: 99%